Midostaurin in daily clinical practice of patients with advanced systemic mastocytosis - Lübke, Johannes; Naumann, Nicole; Brand, Timo; Steiner, Laurenz; Repp, Roland; Metzgeroth, Georgia; Fabarius, Alice; Hofmann, Wolf-Karsten; Radia, Deepti H.; Reiter, Andreas; Schwaab, Juliana (British journal of haematology, 2025)
Midostaurin, a multikinase/KIT inhibitor, is approved for the treatment of advanced systemic mastocytosis (AdvSM). We evaluated dosing regimens, safety, efficacy and overall survival (OS) of 79 patients from the ‘German Registry on Disorders of Eosinophils and Mast Cells’. Midostaurin was initiated at 200 and ≤150 mg daily in 63/79 (80%) and 16/79 (20%) and continued at month 12 in 44/63 (70%) and 10/16 (63%) patients respectively. Over a cumulative observation period of 146 patient-years, 96 adverse events (AE) led to dose adjustment, most commonly nausea/emesis (n = 22, 23%) and neutropenia (n = 8, 8%). Responses were achieved in 60% (modified Valent criteria), 29% (IWG-MRT-ECNM, International Working Group-Myeloproliferative Neoplasms Research and Treatment & ECNM criteria) and 13% (pure pathological response criteria) of patients. Within the first 12 months, achievement of a response was dose independent except for modified Valent criteria. The response duration (modified Valent/IWG-MRT-ECNM criteria) correlated with improved OS (p < 0.001). Midostaurin was ultimately stopped in patients due to lack of response/progression, death and AEs in 28 (39%), 5 (6%) and 13 (17%) patients respectively. Following midostaurin discontinuation, 7/41 (17%) patients experienced a discontinuation syndrome, which was effectively prevented in subsequent patients through dose tapering and corticosteroid bridging. In conclusion, midostaurin demonstrated a favourable safety profile and yielded durable responses in AdvSM patients across dosing regimens.